1997
DOI: 10.1083/jcb.136.4.833
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Participation in the Intracellular Ca2+ Network

Abstract: Calcium can activate mitochondrial metabolism, and the possibility that mitochondrial Ca2+ uptake and extrusion modulate free cytosolic [Ca2+] (Cac) now has renewed interest. We use whole-cell and perforated patch clamp methods together with rapid local perfusion to introduce probes and inhibitors to rat chromaffin cells, to evoke Ca2+ entry, and to monitor Ca2+-activated currents that report near-surface [Ca2+]. We show that rapid recovery from elevations of Cac requires both the mitochondrial Ca2+ uniporter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
413
1
4

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 525 publications
(446 citation statements)
references
References 59 publications
28
413
1
4
Order By: Relevance
“…In addition, uneven distribution of the dye within mitochondria could also occur when using this probe. However, rhodamine‐based fluorescence probes have been extensively used in the literature as a method to assay mitochondrial calcium (Abramov & Duchen, 2003; Babcock, Herrington, Goodwin, Park & Hille, 1997; Boitier, Rea & Duchen, 1999), and we conducted all the experiments accurately and using the appropriate controls.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, uneven distribution of the dye within mitochondria could also occur when using this probe. However, rhodamine‐based fluorescence probes have been extensively used in the literature as a method to assay mitochondrial calcium (Abramov & Duchen, 2003; Babcock, Herrington, Goodwin, Park & Hille, 1997; Boitier, Rea & Duchen, 1999), and we conducted all the experiments accurately and using the appropriate controls.…”
Section: Resultsmentioning
confidence: 99%
“…Minta et al (1989) originally described that Rhod2 accumulate, hydrolyzed and trapped in the mitochondrial compartment. Since then several investigators using fluorescence imaging in single cells preloaded at room temperature have shown that Rhod-2 indeed localized in punctuate and filamentous regions around the nucleus consistent with mitochondrial localization (Babcock et al, 1997;Boitier et al, 1999). Further in chromatoffin cells potassium-induced depolarization induced rapid calcium entry into the mitochondria and increased the Rhod-2 fluorescence within the mitochondria (Babcock et al, 1997).…”
Section: Conclusion and Discussionmentioning
confidence: 90%
“…κ S values 1,000 have been reported for myocytes [58] and various neuronal types [1,23,46,54]. On the other hand, values of 40-100 have been reported for rat chromaffin cells [11,29] and bovine chromaffin cells [40,60,63].…”
Section: ]) the Ratio D[ T Ca]/d[camentioning
confidence: 99%
“…2a). The calciumbinding capacity for Ca 2+ (κ S ) inside the mitochondrial matrix seems to be very high, in the 10 3 range [11,17,29,30]. In addition, it has been proposed recently that precipitation of Ca 3 (PO 4 ) 2 into the matrix con account for additional, almost unlimited, buffering [16,57].…”
Section: Mitochondrial Calcium Transportmentioning
confidence: 99%
See 1 more Smart Citation